THE IMPACT OF LEMONILO GREEN MARKETING ON PURCHASE INTENTION - Riyanto, Ricarhdus Rikky; Sander, Ongky Alex; Megawati, Yenli; Elim, Rickel Arial Kaisar; Cerlysia, Cerlysia (Graduate Program of Universitas Tarumanagara, 2023)
Green marketing concept is getting popular in Indonesia and the world. Various food companies start innovating and launching food brands that use environmentally friendly concept. This research aims to identify impact of environmental concern, attitude toward green products purchase and on Lemonilo purchase intention. This research uses quantitative approach method by using primary data sources from e-questionnaire. The research result shows there is a significant impact of environmental concern on attitude toward green products purchase. The research also found that there is a significant impact of attitude toward green products on Lemonilo purchase intention. However, there is no significant impact of environmental concern on Lemonilo Purchase Intention.